1994
DOI: 10.1007/bf02537091
|View full text |Cite
|
Sign up to set email alerts
|

Effect of maternal dietary arachidonic or linoleic acid on rat pup fatty acid profiles

Abstract: Rapidly growing neonatal mammals accrete relatively large quantities of long chain (> or = C20) polyunsaturated fatty acids (LCP) in membrane phospholipids. We have examined accumulation of omega 6 LCP in suckling neonatal rat pups during the first 14 d of life when their dams received essential fatty acids in the form of triglycerides containing linoleic acid or arachidonic acid. Dietary levels of these fatty acids were either 1 or 5% of total dietary fatty acids. The fatty acid profile of pup stomach content… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
20
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 35 publications
3
20
0
Order By: Relevance
“…This approach has been extensively validated (5,6,27,29,34) and takes into account a small potential for lipolysis in the stomach (12,16,23). Furthermore, it has been suggested that the absorption of lipids and fatty acids in the stomach is negligible (16).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This approach has been extensively validated (5,6,27,29,34) and takes into account a small potential for lipolysis in the stomach (12,16,23). Furthermore, it has been suggested that the absorption of lipids and fatty acids in the stomach is negligible (16).…”
Section: Discussionmentioning
confidence: 99%
“…Only full stomachs were analyzed. The use of contents from full stomachs to reflect the lipid and fatty acid composition of ingested milk has been extensively validated (5,6,27,29,34).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The studies exploring the effects of dietary fatty acids on the membrane composition of the nervous system in the developing rat have investigated the dam's milk composition only on day 14 postpartum (20)(21)(22)(23). They give an incomplete view of the quantity of n-3 fatty acids ingested by the suckling pup because 22:6n-3 decreases during the maturation of milk (17,24).…”
Section: Discussionmentioning
confidence: 98%
“…The comparative effect of maternal dietary fats on tissue fatty acid composition of the fetus [12,13] and suckling pups [12,13,[32][33][34] has been investigated previously. These studies, in unison, demonstrate that tissue fatty acids of rat offspring are altered significantly by maternal diet.…”
Section: Discussionmentioning
confidence: 99%